Potato Annexin STANN1 Promotes Drought Tolerance and Mitigates Light Stress in Transgenic Solanum tuberosum L. Plants - Szalonek, Michal; Sierpien, Barbara; Rymaszewski, Wojciech; Gieczewska, Katarzyna; Garstka, Maciej; Lichocka, Malgorzata; Sass, Laszlo; Paul, Kenny; Vass, Imre; Vankova, Radomira; Dobrev, Peter; Szczesny, Pawel; et al. (PloS one, 2015)
Annexins are a family of calcium- and membrane-binding proteins that are important for plant tolerance to adverse environmental conditions. Annexins function to counteract oxidative stress, maintain cell redox homeostasis, and enhance drought tolerance. In the present study, an endogenous annexin, STANN1, was overexpressed to determine whether crop yields could be improved in potato (Solanum tuberosum L.) during drought. Nine potential potato annexins were identified and their expression characterized in response to drought treatment. STANN1 mRNA was constitutively expressed at a high level and drought treatment strongly increased transcription levels. Therefore, STANN1 was selected for overexpression analysis. Under drought conditions, transgenic potato plants ectopically expressing STANN1 were more tolerant to water deficit in the root zone, preserved more water in green tissues, maintained chloroplast functions, and had higher accumulation of chlorophyll b and xanthophylls (especially zeaxanthin) than wild type (WT). Drought-induced reductions in the maximum efficiency and the electron transport rate of photosystem II (PSII), as well as the quantum yield of photosynthesis, were less pronounced in transgenic plants overexpressing STANN1 than in the WT. This conferred more efficient non-photochemical energy dissipation in the outer antennae of PSII and probably more efficient protection of reaction centers against photooxidative damage in transgenic plants under drought conditions. Consequently, these plants were able to maintain effective photosynthesis during drought, which resulted in greater productivity than WT plants despite water scarcity. Although the mechanisms underlying this stress protection are not yet clear, annexin-mediated photoprotection is probably linked to protection against light-induced oxidative stress.